Analysis of Sediments in the North-East Morainic Upland Edge Zone in the Vicinity of Piaski Pomorskie (West Pomerania, NW Poland) - Paluszkiewicz, Ryszard; Paluszkiewicz, Renata (Quaestiones Geographicae, 2016)
the aim of this article is the description of lithofacies characteristics of sediments forming the north-east part of the morainic upland edge zone in the vicinity of Piaski Pomorskie (west Pomerania). the paper undertake also an attempt to reconstruct paleogeographical conditions of the formation of moranic uppland edge. The diversification of glaciofluvial and fluvial processes during the phase of stagnation and recession of uppervistulian ice-sheet in the vicinity of Piaski Pomorskie (western Pomerania) led to the formation of a morainic upland edge distinctly marked in morphology The edge zone separates the undulating moraine plateau from a lower situated Dębnica River Valley. This area is mostly formed by fine-grained sands with occasional layers of a coarser fraction of gravel and coarse- and medium-grained sands. The observed type of low-angle cross-stratification and trough cross-stratification indicates the dominance of diversified energy depositional environment with considerable power of water as transporting medium. the research area was formed at the front of the ice-sheet, which receded from the nearby reach of the Pomeranian Phase of the weichselian glaciation.